Calculation of the preferences vector of the hierarchical analytical process under the optimization approach (Publicaciones en Ciencias y Tecnología, 2007)
The analytic hierarchy process is a leader tool among multicriteria decision models. Nevertheless, Saaty's eingervector method to find the preferences vector has been criticized. As an alternative we propose a new method to calculate the priority vector based on projection of the priorities matrix on to the set of consistent matrices. We show that our method is well defined, and present numerical evidence that it produces more robust results than Saaty's method.
Keywords: Analytical Hierarchical Process; multi-objective decision making; optimization